Isolation of Keratinophilic Fungi from Soil Samples of Forests and Farm Yards - H Moallaei; F Zaini; M Pihet; M Mahmoudi; J Hashemi (Tehran University of Medical Sciences, 2006)
Soil is well known to support the transient or ongoing existence of kerathophilic fungi and potential sources of infection for humans and animals. Fifty soil samples were collected from various areas of forests and farmyards at Golestan Province in the north part of Iran to determine the prevalence of keratinophilic fungi and dominant species. A total of 357 fungal colonies including 13 genera with 11 species were isolated as follows: Anixiopsis stercoraria (16.24%), Arthroderma cuniculi (12.04%), Reniospora flavissima (9.24%), Fusarium oxysporum (9.24%), Aspergillus flavus (8.68%), Chrysosporium keratinophilum (8.40%), Trichophyton vanbreuseghemii (7.84%), and other fungi (37.56%). McNemar's test showed that non-keratinolytic fungi were dominant in this investigation (P< 0.05). Anixiopsis stercoraria (16.24%) was the most prevalent and dominant keratinophilc fungus (P< 0.05). It can be concluded that soils from forest and farmyards of Golestan Province are rich in keratiophilic fungi including dermatophytes.